2012
DOI: 10.1017/s0266467412000521
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of rain-forest floristic variation on an altitudinal gradient in southern Costa Rica

Abstract: Abstract:The degree to which geographical location rather than environment affects the maintenance of high tropical forest beta diversity on altitudinal gradients is not well understood. Forest composition and its relationship to climate, soil, altitude and geographical distance were determined across an 1114-km2 landscape in south Pacific Costa Rica spanning an altitudinal gradient (0–1500 m asl). In 37 0.25-ha plots, > 200 species of dicot trees (≥ 30 cm dbh) and canopy palms (≥ 10 cm dbh) were found. Ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 63 publications
3
44
1
4
Order By: Relevance
“…Aunque los rangos altitudinales son moderados y no superan los 600 m de diferencia altitudinal, se evidencia una correlación negativa entre altitud y temperatura según el análisis de componentes principales (figura 6). Esta asociación es común en gradientes altitudinales amplias o moderadas dentro de la región tropical (Báez et al 2015, Chain-Guadarrama et al 2012. Bajo esta variación se describieron mayores valores en riqueza y diversidad (figura 3) en la comunidad 3, ubicada en sitios con menores temperaturas y mayores altitudes.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Aunque los rangos altitudinales son moderados y no superan los 600 m de diferencia altitudinal, se evidencia una correlación negativa entre altitud y temperatura según el análisis de componentes principales (figura 6). Esta asociación es común en gradientes altitudinales amplias o moderadas dentro de la región tropical (Báez et al 2015, Chain-Guadarrama et al 2012. Bajo esta variación se describieron mayores valores en riqueza y diversidad (figura 3) en la comunidad 3, ubicada en sitios con menores temperaturas y mayores altitudes.…”
Section: Discussionunclassified
“…Castellanos-Castro y Newton (2015) encontraron que el potasio, pH, nitrógeno y el sodio del suelo explican significativamente la variación florísti-ca y distribución altitudinal de especies arbóreas (Unger et al 2012). Esta variación florística también es explicada por la distancia geográfica que influye en la limitación o facilitación de la dispersión de especies (Chust et al 2006, Chain-Guadarrama et al 2012. En los bosques andinos de Sudamérica el incremento del área basal está relacionada negativamente con la altitud y posibles efectos de las bajas temperaturas que influyen sobre el metabolismo fotosinté-tico de las plantas (Báez et al 2015).…”
Section: Introductionunclassified
“…The composition of plant species is a floristic list of plant species that exist in a community (Koike, 2010;Guadarrama et al, 2012;Carim et al, 2015). The results showed the number of species, genera, and families of vegetation present in plots varied by land type, both at the tree level (height >1.5 m) and at the level of low seedlings/plants (Fig.…”
Section: Species Composition Of Vegetationmentioning
confidence: 99%
“…Thus, Kitayama (1992) identified four altitudinal vegetation zones on Mount Kinabalu, Borneo, made up by "mutually exclusive" groups of species. The strong correlations between altitude, climate, and other environmental factors, especially soil, continue to represent a major challenge to complete understanding of the response of forest vegetation to altitude (Chain-Guadarrama, Finegan, Vilchez, & Casanoves, 2012;Grubb, 1977;Malhi et al, 2010). On the other hand, Lieberman, Lieberman, Peralta, and Hartshorn (1996), suggested that rain forest composition varies linearly with altitude over a 100 m to 2,600 m asl.…”
Section: Introductionmentioning
confidence: 99%